A comparison of methods to measure central and peripheral oxytocin concentrations in human and non-human primates. Issue 1 (December 2017) - Lefevre, Arthur; Mottolese, Raphaëlle; Dirheimer, Manon; Mottolese, Carmine; Duhamel, Jean-René; Sirigu, Angela
Abstract Oxytocin (OT) concentration in the blood is considered to be a marker of its action in the brain. However, two problems have emerged when measuring OT level in the blood. First, it is unclear whether different methods of assessment lead to similar OT values. Second, it is unclear if plasma OT concentrations is informative on what OT does in the brain. To clarify these issues, we collected cerebrospinal fluid (CSF) from the brain ventricle of 25 patients during surgery to compare with plasma OT after simultaneous blood withdrawal. Additionally, we collected 12 CSF and blood samples from non-human primates while awake or under anaesthesia. We used four methods to assay OT concentrations: Commercial EIA with/without extraction, laboratory developed EIA with filtration and RIA with extraction. Three of these methods showed a positive correlation between plasma and CSF OT, suggesting a link between plasma and central OT, at least under specific testing conditions. However, none of the methods correlated to each other. Our results show major disagreements among methods used here to measure peripheral and brain OT and therefore they call for more caution when plasma OT is taken as a marker of central OT.